Using LEGO NXT Mobile Robots With LabVIEW for Undergraduate Courses on Mechatronics. - Gómez-de-Gabriel, Jesús Manuel; Mandow, Anthony; Fernández-Lozano, Juan Jesús; García-Cerezo, Alfonso José (IEEE, 2010)
The paper proposes lab work and student competitions based on the LEGO NXT Mindstorms kits and standard LabVIEW. The goal of this combination is to stimulate design and experimentation with real hardware and representative software in courses where mobile robotics is adopted as a motivating platform to introduce mechatronics competencies. Basic LabVIEW examples are proposed for three case-study laboratory practices. These are implemented with the NXT Toolkit and the NXT Direct Command programming libraries for standalone and remote execution, respectively. The application of this instructional material has been tested in two different experiences with senior undergraduate engineering students. A description of the courses as well as an assessment of student results are also included.
https://openpolicyfinder.jisc.ac.uk/id/publication/3440
Keywords: Robótica; Tecnología educativa; Ingeniería - Estudio y enseñanza; Robots - Programación; Aprendizaje basado en proyectos; Mechatronics; Educational robots; Mobile robots; Education; Robot sensing systems; Engineering education; LabVIEW; LEGO Mindstorms NXT; Project-based learning; Robot programming